ReCODE integrated collaborative mind mapping to improve students’ creative thinking skill - Kalimatul Maghfiroh; Susriyati Mahanal; Sitoresmi Prabaningtyas (Journal of Research in Instructional, 2025)
This study aims to determine the effect of reading, connecting, observing, discussing, and evaluating (ReCODE) model integrated with collaborative mind mapping (CMM) on creative thinking skills of high school students in biology learning. This quasi-experimental study used a pretest-posttest nonequivalent control group design. There were 10 description questions used in assessing students' creative thinking skills. Data were collected from 106 students of class XI at senior high school in Sidoarjo, Indonesia. The data were analyzed using ANCOVA at 5% significance level followed by LSD test. The results showed that the ReCODE-CMM learning model had an effect on students' creative thinking skills. The conclusion of this study is that the ReCODE-CMM model is able to improve each indicator of creative thinking skills because the components of this indicator have been integrated into the syntax of the learning model which involves the process of reading, linking concepts and facts in the problem, and organizing information collaboratively to create a solution to a problem.